2000
DOI: 10.1029/1999gl010870
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of retrieved POLDER directional cloud optical thickness to various ice particle models

Abstract: The ”directional” values of cloud optical thickness (or cloud spherical albedo) retrieved from ADEOS‐POLDER data constitute a strong constraint on the microphysical model used in the retrieval algorithm. In this paper, we focus on ice clouds. We quantify the departure of the directional values of spherical albedo from their averaged value. By so doing, we can assess the suitability of different ice particle scattering models (i.e., spheres, fractal polycrystal, inhomogeneous hexagonal monocrystal, or a synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 11 publications
5
49
0
Order By: Relevance
“…7b. Several previous studies have also noticed such a resemblance (e.g., Doutriaux-Boucher et al, 2000;C.-Labonnote et al, 2001;Knap et al, 2005;Baran and Labonnote, 2006). However, the reason behind this resemblance still remains unexplained.…”
Section: Potential Implications For the Derivation Of Seasonal Variatmentioning
confidence: 85%
See 2 more Smart Citations
“…7b. Several previous studies have also noticed such a resemblance (e.g., Doutriaux-Boucher et al, 2000;C.-Labonnote et al, 2001;Knap et al, 2005;Baran and Labonnote, 2006). However, the reason behind this resemblance still remains unexplained.…”
Section: Potential Implications For the Derivation Of Seasonal Variatmentioning
confidence: 85%
“…The Baum05 model also provides a connection between ice particle optical properties with the measured environmental conditions, such as the temperature and humidity, which are the key variants in the ice cloud parameterization schemes for GCMs (Donner et al, 1997;Kristjánsson et al, 2000). A very attractive advantage of the IHM model has been demonstrated in many studies Doutriaux-Boucher et al, 2000;C.-Labonnote et al, 2001;Baran and Labonnote, 2006). These studies showed that based on the IHM model consistent ice cloud spherical albedos are retrieved from POLDER observations at different viewing directions, while use of a scattering phase function based on pristine and smooth ice hexagonal columns or plates such as those used in Baum05 model may lead to inconsistent retrievals.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latitudinal distribution of the POLDER pixels and the scattering angle range used in this paper are shown in Table VII. The methodology used to test the ensemble model has been previously described in Labonnote et al (2001) and the radiative-transfer model used in this section is described in Doutriaux-Boucher et al (2000). However, a brief description of the methodology is given here.…”
Section: Testing the Ensemble Model's Prediction Of Total Reflection mentioning
confidence: 99%
“…It has been previously demonstrated that the best phase function to apply to the remote sensing of cirrus is one that is generally featureless and flat at backscattering angles (Foot, 1988;Baran et al, 1999;Francis et al, 1999;Knap et al, 1999;Doutriaux-Boucher et al, 2000;Baran et al, 2001;Labonnote et al, 2001;Baran et al, 2003;Field et al, 2003a;Jourdan et al, 2003;Ulanowski et al, 2003;Baran and Francis, 2004;Baran et al, 2005;Knap et al, 2005;Baran and Labonnote, 2006;Shcherbakov et al, 2006;Ulanowski et al, 2006). In order to theoretically generate featureless phase functions (i.e.…”
Section: Introductionmentioning
confidence: 99%